Real‐world effectiveness of elbasvir/grazoprevir In HCV‐infected patients in the US veterans affairs healthcare system. Issue 11 (3rd July 2018) - Kramer, J. R.; Puenpatom, A.; Erickson, K. F.; Cao, Y.; Smith, D.; El‐Serag, H. B.; Kanwal, F.
Summary: Elbasvir/grazoprevir (EBR/GZR) is an all‐oral direct‐acting antiviral agent (DAA) with high sustained virologic response (SVR) in clinical trials. This study's primary objective was to evaluate effectiveness of EBR/GZR among HCV‐infected patients in a real‐world clinical setting. We conducted a nationwide retrospective observational cohort study of HCV‐infected patients in the US Department of Veterans Affairs (VA) using the VA Corporate Data Warehouse. The study population included patients with positive HCV RNA who initiated EBR/GZR from February 1 to August 1, 2016. We calculated the 95% confidence interval for binomial proportions for SVR overall and by demographic subgroups. Clinical and demographic characteristics were also evaluated. We included 2436 patients in the study cohort. Most were male (96.5%), African American (57.5%), with mean age of 63.5 (SD = 5.9) and 95.4% infected with genotype (GT) 1 [GT1a (34.7%), GT1b (58.6%)]. Other comorbidities included diabetes (53.2%), depression (57.2%) and HIV (3.0%). More than 50% had history of drug or alcohol abuse (53.9% and 60.5%, respectively). 33.2% of the cohort had cirrhosis. A total of 95.6% (2, 328/2, 436; 95% CI: 94.7%‐96.4%) achieved SVR. The SVR rates by subgroups were: male, 95.5% (2245/2350); female, 96.5% (83/86); GT1a, 93.4%, GT1b, 96.6%, GT4, 96.9%, African American, 95.9% (1, 342/1, 400); treatment‐experienced, 96.3% (310/322); cirrhosis, 95.6% (732/766); stage 4‐5 CKD, 96.3% (392/407); and HIV, 98.6% (73/74). SVR rates were high overall and across patient subgroups regardless of gender, race/ethnicity, cirrhosis, renal impairment or HIV. This study provided important data regarding the effectiveness of EBR/GZR in a large clinical setting.